The role of serum inflammatory modulators and the gut microbiome in musculoskeletal trauma - Zheng, Amy Sulan (2025)
Introduction Trauma is one of the leading causes of death in the world, the underlying inflammatory response and biological response to trauma is through to be related to the inflammatory cascade and is regularly monitored clinically in the form of physiological signs and symptoms. Surgery for traumatic injuries is common and there is emerging evidence that the gut microbiome has a part to play in the outcomes associated with traumatic injury. This thesis aims to understand the physiology behind trauma in the context of high-energy rib fracture patients and utilises the inflammatory cytokines, bioactive lipids and endocannabinoids within serum as biomarkers to predict disease and pain.